2017
DOI: 10.20333/2500136-2017-2-97-103
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients With Arterial Hypertension Influencing to the Achievement of Target Pressure: Data of Polyclinics of the Working Village

Abstract: The aim of the research. To reveal the clinical characteristics influencing to the achievement of target BP in patients with AH, observed in the polyclinic of the working village of the Saratov region. Material and methods. The data of outpatient cards of 182 patients with essential hypertension (mean age 64.6 ± 11.3 years, 48.5%-men) were studied, they asked for medical care in the polyclinic of the working village of the Saratov region in the period from 01.07.2015 to 31.07 .2015-the first stage (n = 88) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was also found that hypertension is more common among older females than among older males [4]. It is known that this disease requires constant monitoring and strict adherence to medically prescribed medications to reduce the risk of cardiovascular [5] and renal disease [6]. Besides this, health professionals emphasize the need to find effective strategies for the treatment and care of elderly patients with hypertension [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that hypertension is more common among older females than among older males [4]. It is known that this disease requires constant monitoring and strict adherence to medically prescribed medications to reduce the risk of cardiovascular [5] and renal disease [6]. Besides this, health professionals emphasize the need to find effective strategies for the treatment and care of elderly patients with hypertension [7,8].…”
Section: Introductionmentioning
confidence: 99%